Is Oreochromis niloticus invading the Samborombón Bay, Río de la Plata, Argentina? - García, Mirta L. (2010)
The Nile tilapia (Oreochromis niloticus) is a species widely cultivated worldwide. In recent decades it was an increasing development of fish farming of this species and the red variety in Argentina and Uruguay. From January to March 2010, four specimens of O. niloticus were captured in the south boundary of Samborombón Bay (S 36° 17´- W 56° 46´), which is the external sector of the Río de la Plata. Probably the collected specimens were released accidentally from hatcheries placed on the banks of aquatic environments in communication with the Samborombón Bay. The patterns and mechanisms of species dispersal are of significant interest, while the interactions among factors determining invasion success often remain poorly understood. Invasion success is influenced by the ability of invading specie to withstand, interactions with native species and oceanographic characteristics of the new habitat. Of four specimens obtained two were females, one in spawning stage. This is the first record of Nile tilapia from a natural environment in Argentina and could indicate the beginning of a new invasion by a non native species.